The Significance of Didactic Games in the Development of Written Speech in Children - Kholdorova Iroda Valijonovna; Usmonova Ozoda Jahongir kizi (Zien Journals, 2023)
The article reveals the theory of didactic games, which includes the relevance, significance of didactic games in the development of children, the educational value of didactic games. The material is presented from the experience of my work "Didactic games and exercises in the mental development of children." Key words: didactic games, mental education, preschooler, development, education, games.
Keywords: written speech; didactic games; child development